Metaverse Marketing: A Critical Analysis of the Potential and Challenges of Marketing in Virtual Worlds - Syaifuddin, Syaifuddin (PT Inovasi Pratama Internasional, 2025)
The emergence of the metaverse as an immersive three-dimensional virtual space marks a new phase in global digital transformation. Behind the enthusiasm for its innovative potential, marketing strategies in the metaverse face unresolved issues, particularly related to digital literacy gaps, the absence of specific biometric regulatory frameworks, and the lack of organizational readiness to manage brand-consumer interactions in the virtual world. This complexity creates a gap between the appeal of the technology and the reality of digital marketing implementation in the metaverse. This study aims to systematically examine the potential and challenges of metaverse marketing and its implications for the success of brand communication strategies. The method used is a Systematic Literature Review (SLR) with a descriptive qualitative approach. Literature was obtained from reputable academic databases such as Scopus, ScienceDirect, Emerald Insight, SpringerLink, and SINTA. The articles reviewed were scientific publications in Indonesian and English relevant to digital marketing, data protection, and metaverse ecosystem development. Article selection was conducted through an initial screening of titles and abstracts, followed by a thorough reading of the article content. This resulted in 35 primary sources analyzed through thematic synthesis based on the PRISMA protocol and Kitchenham framework. The study findings indicate that the metaverse offers strategic opportunities for creating immersive and community-based brand experiences. However, the effectiveness of digital marketing strategies heavily depends on an organization's ability to navigate challenges related to privacy, avatar ethics, and technological limitations. Therefore, a holistic approach that integrates innovation, ethics, and infrastructure readiness is needed to ensure successful marketing in the metaverse.